School Communication Planning in Improving Teacher Performance at SMA Negeri 1 Ngunut Tulungagung - Ubaidillah, Adhis; Naim, Ngainun; Badruzaman, Abad (International Journal of Educational Research & Social Sciences, 2024)
Managing a school to progress requires various efforts and strategies that support each other. It requires hard work, cooperation and optimization from every line. Communication is needed to manage the organization so that the vision and mission can be achieved. Establishing good communication between members of the organization can create a conducive work climate, effective work mechanisms and of course involve all related elements in the organization. With good communication, an institution can run smoothly, successfully and vice versa. This research uses a qualitative approach, with a multi-case design. Data collection techniques using in-depth interviews, participant observation and documentation. Data analysis uses the Miles Huberman model of data presentation, data condensation, and conclusion drawing. Test the validity of the data through credibility, transferability, dependability, and confirmability. The results of the findings at the research location regarding communication planning in improving teacher performance at SMA Negeri 1 Ngunut are as follows: Communication planning will improve teacher performance if it is carried out at the beginning of each year, incidental and routine planning, with a POAC pattern at every event, thorough problem solving, one way communication and two way communication, individual, group, coaching, and internal school MGMP, formal and informal, large meetings, flexible family communication, mandates, and confirmation of Decree (SK).